Alligator appendicular architecture across an ontogenetic niche shift. Issue 10 (26th July 2021) - Hedrick, Brandon P.; Schachner, Emma R.; Dodson, Peter
Abstract: A variety of species undergo ontogenetic niche shifts in either diet, habitat, or both. As a result, multiple ontogenetic stages are able to take advantage of different resources and live in sympatry without competing with one another. The American alligator ( Alligator mississippiensis ) begins to undergo an ontogenetic niche shift in both diet and habitat at a length of 1.2 m. They transition from a terrestrial wetland environment to a riverine environment and take advantage of different dietary resources. At 1.8 m, A . mississippiensis reaches sexual maturity. Ontogenetic shifts in habitat have the capacity to alter morphology, especially limb morphology, as different age classes traverse different ecological systems. We evaluated shape trends in the scapulae, humeri, ilia, and femora using geometric morphometrics to test whether there were punctuated changes in limb shape, shape disparity, and integration corresponding to either the ontogenetic habitat shift or onset of sexual maturity. We found size to strongly correlate with limb shape but found a continuous size gradient rather than punctuated changes in size. Furthermore, we found that adults (total length > 1.8 m) had significantly higher limb shape disparity than juveniles or subadults, likely related to ontogenetic decreases in limb use and a reduction in limb constraints. Finally, we found that the forelimb and hindlimb acted as a single integrated unit and that neither the forelimb nor hindlimb was significantly more integrated than the other. Therefore, the ontogenetic niche shift itself did not impact limb morphology in A . mississippiensis .